Novi terminološki slovarji - Šega, Lidija (Mostovi (Ljubljana), 2006)
In the article, the following works are briefly presented: Dictionary of Marketing, Dictionary of Public Purchasing and Dictionary of Insurance Business.
Keywords: javno naročanje; ocene in poročila; terminološki slovarji; trženje; zavarovalništvo